Объяснение:
1) NH4Cl + NaOH = NaCl + NH3 + H2O
NH4(+)+ Cl(-)+ Na(+) + OH(-) = Na(+) + Cl(-)+ NH3 + H2O
NH4(+)+ OH(-) = NH3 + H2O
2) NH4OH + HCl = NH4Cl + H2O
NH4OH+ H(+)+ Cl(-)= NH4(+)+ Cl(-)+ H2O
NH4OH + H(+) = NH4(+) + H2O
3) Na2CO3 + 2HCl = 2NaCl + CO2 + H2O
2Na(+) + CO3(2-) + 2H(+) + 2Cl(-) = 2Na(+) + 2Cl(-) + CO2 + H2O
CO3(2-) + 2H(+) = CO2 + H2O
4) Pb(OH)2 + 2NaOH = Na2PbO2 + 2H2O
Pb(OH)2 + 2Na(+) + 2OH(-) = 2Na(+) + PbO2(2-)+ 2H2O
Pb(OH)2 + 2OH(-)= PbO2(2-) + 2H2O
5) Cd(NO3)2 + 2NaOH = Cd(OH)2 + 2NaNO3
Cd(2+) + 2NO3(-)+ 2Na(+) + 2OH(-) = Cd(OH)2 + 2Na(+) + 2NO3(-)
Cd(2+) + 2OH(-)= Cd(OH)2
6) CO2 + 2NaOH = Na2CO3 + H2O
CO2 + 2Na(+) + 2OH(-) = 2Na(+) + CO3(2-) + H2O
CO2 + 2OH(-) = CO3(2-) + H2O
0,5 моль Х л
Са + H2SO4 = CaSO4 + H2
n = 1 моль n = 1 моль
Vm=22,4 л/моль
V=22,4 л
0,5 моль Са - Х л Н2
1 моль Са - 22,4 л Н2
V(H2) = 0,5 * 22,4 = 11,2 л
Объяснение:
1) NH4Cl + NaOH = NaCl + NH3 + H2O
NH4(+)+ Cl(-)+ Na(+) + OH(-) = Na(+) + Cl(-)+ NH3 + H2O
NH4(+)+ OH(-) = NH3 + H2O
2) NH4OH + HCl = NH4Cl + H2O
NH4OH+ H(+)+ Cl(-)= NH4(+)+ Cl(-)+ H2O
NH4OH + H(+) = NH4(+) + H2O
3) Na2CO3 + 2HCl = 2NaCl + CO2 + H2O
2Na(+) + CO3(2-) + 2H(+) + 2Cl(-) = 2Na(+) + 2Cl(-) + CO2 + H2O
CO3(2-) + 2H(+) = CO2 + H2O
4) Pb(OH)2 + 2NaOH = Na2PbO2 + 2H2O
Pb(OH)2 + 2Na(+) + 2OH(-) = 2Na(+) + PbO2(2-)+ 2H2O
Pb(OH)2 + 2OH(-)= PbO2(2-) + 2H2O
5) Cd(NO3)2 + 2NaOH = Cd(OH)2 + 2NaNO3
Cd(2+) + 2NO3(-)+ 2Na(+) + 2OH(-) = Cd(OH)2 + 2Na(+) + 2NO3(-)
Cd(2+) + 2OH(-)= Cd(OH)2
6) CO2 + 2NaOH = Na2CO3 + H2O
CO2 + 2Na(+) + 2OH(-) = 2Na(+) + CO3(2-) + H2O
CO2 + 2OH(-) = CO3(2-) + H2O